Pengaruh Metode Pembelajaran Cooperative Script Terintegrasi Al-Qur’an pada Konsep Sistem Reproduksi terhadap Hasil Belajar Siswa Kelas XI SMAS Al-Washliyah 3 Medan - Hastina Rusda; Ira Suryani; Efrida Pima Sari Tambunan (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
This study aims to determine the differences in student learning achievement between the control class and the experimental class, and to determine the effect of the Integrated Cooperative Script Al-Quran Learning Method on the Concept of the Reproductive System on the Learning Outcomes of Class XI Students of SMAS Al-Washliyah 3 Medan. The method used is an experiment whose implementation uses a quasi-experiment type with a nonequivalent control group design. The study population consisted of 48 students, namely class XI IPA-1 totaling 26 students and class XI IPA-2 totaling 22 students. Less than ideal results were observed for learning outcomes in the control class when the Cooperative Script Learning Method was not integrated with the Qur'an. An average of 78.6 describes the learning objectives. The Cooperative Script Learning Method Integrated with the Qur'an resulted in an increase in learning outcomes in the experimental class. The average (85.7), mode (87) and median (87), maximum value (97), and lowest value (75) all indicate learning outcomes. At a 5% error rate, the calculation of the independent sample t-test revealed that t table < t count (3.07 > 2.01). The experimental class had a higher percentage increase from pretest to posttest (85.15%) compared to the control class (77.98%). Therefore, the implementation of the Cooperative Script learning approach effectively contributed 55% of the total. Thus, it can be said that the learning outcomes of the experimental class that utilized the Integrated Cooperative Script Al-Quran Learning Method and the learning outcomes of the control class that used the Non-Integrated Cooperative Script Al-Quran Learning Method were significantly different.